Confucian Ideas and Russian Culture of the XVIII Century on the Example of “Description of the Life of Confucius, the Head of Chinese Philosophers” - D. V. Tsvetkov (Библиосфера, 2022)
The influence of Confucian ideas on intellectual life in Russia of the XVIII century has not been studied enough and needs more detailed research. This paper is about the research of text “Description of life of Confucius, head of Chinese philosophers”. The purpose of the article is to identify the background of its creation, analyze the translation of this text and establish its connection with the ideas of the Enlightenment era. It was revealed that the “Description of the Life of Confucius ...” is a collection of fragments from the texts of “Lun yu” and “Zhong Yun” of the Confucian “Four books”, the Latin translation of which was placed in “Confucius Sinarum philosophus, sive Scientia Sinensis” (“Confucius, the philosopher of the Chinese, or Chinese science”) – work, in which, for the first time, traditional Chinese philosophical teachings are systematized. The nature of the fragments, the principle of their grouping by chapters, as well as the topics of the chapters indicate that “The Description of the life of Confucius ...” could act as a lesson to young people preparing for public service. Such an appointment of the “Description of the life of Confucius ...” seems most likely, if we also take into account the tendency that took place in the intellectual environment of the XVIII century to compile manuals on the education of young people corresponding to the ideals of Enlightenment.